Problem intabulacji prawa własności nieruchomości w Polsce (w byłym zaborze austriackim) w okresie międzywojennym - Koredczuk, Józef (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
Entering the property rights in the land book in the law of the former Austrian Partition in Poland in the interwar period, i.e. intabulation, was of great importance. It was one of the conditions for the effective transfer of that right. This also applies to the transfer of ownership of real estate by inheritance. In practice, unfortunately, it was often not carried out, which caused adiscrepancy between the actual and legal state of ownership of real estate. Even the courts had to be reconciled with this situation. It occurred in the former Austrian partition, especially regarding the inheritance of peasant land, giving rise to many legal problems.
Keywords: ABGB; inheritance; intabulation; land book; transfer of ownership; ownership of real estate